Pengaruh Training Terhadap Kinerja Karyawan Housekeeping Department Hotel Ibis Styles Malang - Kariyoto Dr (Jurnal VOK@SINDO, 2018)
The aim of this study is to explain partial and simultaneous influence of training on the performance of the employees. The training aspect covers training materials, training methods, and the continuous implementation after training. This explanatory study involved 22 employees. The result shows that training materials, training methods, and the continuous implementation after training have significant influence on the employee performance as shown with the results of simultaneous test with the value signivicance F and t (0,000) ≤ (p<0.05). Training employees partially and simultaneously have a positive effect on employee performance.